Hubungan Perilaku Makan dan Konsumsi Tablet Fe dengan Kejadian Anemia pada Ibu Hamil di Kabupaten Fakfak Papua Barat - Kristiawan P.A. Nugroho; Windu Merdekawati; Julia Mariyani Hekakaya (LPPM STIKES Guna Bangsa, 2017)
Background: Anemia is associated with a condition of blood deficiency or low red blood cell count. Anemia during pregnancy is important to note because it concerns public health, especially maternal and child health. Objective: This study was to determine the relationship between eating behavior, iron tablet consumption, and anemia incidence in pregnant women in three Health Center (Puskesmas) in Fakfak district, West Papua. Methods: This study used quantitative method with cross sectional study design. The total samples were 55 respondents from Fakfak Kota Health Center, Dulanpokpok Health Center, and Danaweria Health Center. Results: Not all pregnant women were found to be regularly taking Fe tablets with a significance value of Chi-Square test of 0.001, so that unregulary consumption of Fe tablets can affect the incidence of anemia in pregnant women. Conclusion: There is a relationship of consumption of Fe tablets with anemia during pregnancy, not eating behavior.